Discrete Working Time Choice in an Applied General Equilibrium Model - Nicole Gürtzgen; Michael Feil; Stefan Boeters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
We present a model that integrates the discrete working time choice of heterogenous households into a general equilibrium setting where wages are determined by sectoral bargaining between firms and trade unions. The model is calibrated to German micro and macro data. We then use it to analyse stylised policy reforms that are designed to stimulate labour supply.
Keywords: J22; J51; D58; 330; applied general equilibrium; discrete working time choice; labour market; trade unions; wage bargaining; labour market reform; Arbeitszeit; Arbeitsangebot; Haushaltsökonomik; Lohnverhandlungen; Allgemeines Gleichgewicht; Arbeitsmarktflexibilisierung; Theorie; Deutschland